Agus Hasan Bashori’s Innovation in the Development of Hadith Science in Indonesia - Pelangi Cahya Indah Putriana; Shabrina Setiawan; Fadhila Salma Nuzula; Iskandar Iskandar (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
Hadith figures have a wide scope. Individuals who play an important role in the collection, compilation, and study of hadith can be defined as hadith figures. This article examines the significant contribution of Agus Hasan Bashori in the development of hadith science through his work entitled al-Arba'un an-Nawawiyah wa Ziyaadatuha ar-Rajabiyah. The purpose of this study is to find Agus Hasan Bashori's innovation in assessing, listing, and compiling the hadith fawaid of Imam Nawawi and Imam Ibn Rajab by comparing the tahqiq results of the scholars. This research uses a qualitative approach with the type of biographical study research interview technique. The results of this study indicate that: (1) The role of a family that has positive values related to education, hard work, and integrity is one of the supporting factors for Agus Hasan Bashori in achieving his success. (2) Agus Hasan Bashori's exemplary work in accordance with existing principles and values is able to strengthen his character so that it can bring inspiration in the lives of others and build deep trust and respect from others. (3) Agus Hasan Bashori's innovations in Kitab al-Arba'un an-Nawawiyah wa Ziyaadatuha ar-Rajabiyah not only strengthen the scientific foundation of hadith, but also help Muslims integrate the teachings of the Prophet Muhammad into their daily lives and improve their spiritual and moral quality.